(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
Endometrial hyperplasia is a condition characterized by abnormal thickening of the endometrium (uterine lining). It is often caused by an excess of estrogen without adequate progesterone, leading to overgrowth of endometrial cells. This condition can range from simple hyperplasia, which is generally not cancerous, to complex atypical hyperplasia, which carries a higher risk of progressing to endometrial cancer. The diagnosis typically involves endometrial biopsy, and treatment options include hormonal therapy with progestins, such as oral progestins or intrauterine devices (IUDs) containing levonorgestrel, or surgical intervention with hysterectomy in cases of atypical hyperplasia or failure of hormonal therapy. Regular monitoring and follow-up are essential to prevent progression to malignancy. This summary provides an overview of endometrial hyperplasia, its diagnosis, and management strategies.